Continuous Rifampicin Therapy Induced Acute Kidney Injury in a Tuberculous Patient: A Case Report - Muqsit Ali Shaukat; Muhammad Fahad Ali; Ahmed Irtaza; Shehroz Yar Khan; Shad Muhammad Khan; Sohail Babar (University Library System, University of Pittsburgh, 2024)
Background: Tuberculosis (TB) presents with productive cough, hemoptysis, chest pain, fever, weight loss, and night sweats. Anti-tuberculosis treatment (ATT) can affect various organs, including the liver and kidneys. ATT-induced acute kidney injury (AKI) presents with fever, rash, nausea, vomiting, diarrhea, and abdominal pain. It occurs due to type 2 or 3 hypersensitivity and affects individuals who have previously used rifampicin or are currently using it intermittently. Case: An 60-year-old lady was diagnosed with TB and started on ATT. After a few days, she complained of reduced food intake and vomiting, yellow discoloration of the skin, abdominal pain and distention, and limb swelling. She was diagnosed as a case of ATT-induced AKI. She didn't have past exposure to rifampicin and was continuously using it this time. Conclusion: The key learning point from this case is that ATT-induced AKI can develop even when used in a continuous dosing regime and upon first time exposure despite no history of past exposure. This prompts vigilance in monitoring renal function in patients being started on ATT regimen. This is becasuse, ATT-induced AKI poses risk to patient's life and there is a possibility of developing resistance to anti-tuberculous therapy as a result of discontinuation of treatment. Furthermore, our case suggests that, in addition to immune-mediated mechanisms described in literature for ATT-induced AKI, other pathophysiological mechanisms might also be linked to this pathology and need further research for better understanding and optimization of treatment strategies.